2013
DOI: 10.4103/0970-9290.118016
|View full text |Cite
|
Sign up to set email alerts
|

B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma: Report of a case in the oral cavity

Abstract: B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma (DLBCL/BL) is a new category of B-cell lymphoma according to the 4 th edition of the World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissues (2008). The following report presents a case of this rare, newly described entity on the palate of a 59 year-old male.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…This type of lymphoma was newly categorized in the 4th edition of WHO Classification of Tumours of Hematopoietic and Lymphoid Tissues [31] and is a poorly characterized entity [8]. Its occurrence in the oral cavity has been reported recently [7] [32], to our knowledge, our case is the first report of the entity arising in the mandibular region.…”
Section: Pathological Diagnosismentioning
confidence: 64%
See 1 more Smart Citation
“…This type of lymphoma was newly categorized in the 4th edition of WHO Classification of Tumours of Hematopoietic and Lymphoid Tissues [31] and is a poorly characterized entity [8]. Its occurrence in the oral cavity has been reported recently [7] [32], to our knowledge, our case is the first report of the entity arising in the mandibular region.…”
Section: Pathological Diagnosismentioning
confidence: 64%
“…There have been several reportes of malignant lymphoma of the mandible and many of them were aggressive with a poor prognosis [3] [6]. Malignant lymphoma has been reviewed and newly categorized in the latest edition of the World Health Organization (WHO) Classification of Tumours of Haematopoietic and Lymphoid Tissues [7]. Early diagnosis and treatment of the disease confer a better prognosis [3] [6].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Oral involvement by lymphoma may represent a local disease process but more frequently is part of a widespread disease that may also involve the lymph nodes of head and neck region. [ 8 ] Primary lymphomas in the head and neck region represent the second most[ 1 8 ] /third most[ 9 ] common malignancies after squamous cell carcinomas and salivary gland tumors and constitutes 2.2% of all malignancies of the head-neck and 3.5% of intraoral malignancies. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…Jaradat et al [20] reported a case of BCLu-DLBCL/BL involving the oral cavity. Ahn et al [21] reported a case report of BCLu-DLBCL/BL involving the femur neck in a korean child.…”
Section: Discussionmentioning
confidence: 99%